2011
DOI: 10.1186/1756-0500-4-418
|View full text |Cite
|
Sign up to set email alerts
|

An innovative method to assess clinical reasoning skills: Clinical reasoning tests in the second national medical science Olympiad in Iran

Abstract: BackgroundClinical reasoning plays a major role in the ability of doctors to make a diagnosis and reach treatment decisions. This paper describes the use of four clinical reasoning tests in the second National Medical Science Olympiad in Iran: key features (KF), script concordance (SCT), clinical reasoning problems (CRP) and comprehensive integrative puzzles (CIP). The purpose of the study was to design a multi instrument for multiple roles approach in clinical reasoning field based on the theoretical framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…The fact that interns' CRP average score at the highest level was half of the total score may indicate that they were not a good representative of their level of expertise. Moreover, previous studies that assessed clinical reasoning in interns with CRP showed the same results (18,22,23).…”
Section: Discussionsupporting
confidence: 61%
“…The fact that interns' CRP average score at the highest level was half of the total score may indicate that they were not a good representative of their level of expertise. Moreover, previous studies that assessed clinical reasoning in interns with CRP showed the same results (18,22,23).…”
Section: Discussionsupporting
confidence: 61%
“…These shortcomings were prevented in the Reasoning 4 Change instrument by the use of a well-tested format, the inclusion of theory-and evidencebased clinical reasoning capabilities and skills, standardized case scenarios, and predetermined acceptable reasoning paths. Furthermore, the use of complementary methods, such as the Script Concordance Test and the Key Feature approach, may provide a more comprehensive appraisal of the characteristics of clinical reasoning than the use of either of these measures alone (Amini et al, 2011;Groves, Dick, McColl, and Bilszta, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The design of the National Medical Science Olympiad in Iran is focused on critical thinking among medical students. The first Olympiad was held in Isfahan in 2009, and the second in Shiraz in 2010 [ 12 , 13 ]. The specific goals of the Olympiad were competition to achieve the following: identifying and encouraging scientifically talented students; generating scientific morale; helping students gain closer familiarity with scientific culture; cultural exchanges among students; encouraging teamwork to develop creative and critical thinking; reinforcing the goals and objectives of the health system; further the development of interdisciplinary activities [ 12 ].…”
Section: Methodsmentioning
confidence: 99%